Study guides

☆☆

Q: What is 6x3-5x2 plus 7x3 plus 4x2?

Write your answer...

Submit

Still have questions?

Related questions

x(7x ^2 - 4x + 8)

4x2 plus 3=11

The four solution values of x of 3x4 + 7x3 + 4x2 = 0 are: x = -11/3, -1, 0 (repeated) 3x4 + 7x3 + 4x2 = 0 ⇒ x2(3x2 + 7x + 4) = 0 ⇒ x2(3x + 4)(x + 1) = 0 ⇒ x2 = 0 → x = 0 (repeated) or (3x + 4) = 0 → x = -4/3 = -11/3 or (x + 1) = 0 → x = -1

Terms like 2x and 4x2 are not like terms. In order for terms to be like terms, they must have the exact same variables with the exact same exponents on them. This means that 5x3 and 7x3 are like terms, but 2x and 4x2 are not. To add or subtract like terms, simply add or subtract the coefficients (the numbers in front) and keep the variable part the same. For example, 5x3 + 7x3 = (5 + 7)x3 = 12x3, and 3x2 + 6x2 = (3 + 6)x2 = 9x2. But, since 2x and 4x2 are not like terms, 2x + 4x2 = 2x + 4x2. It just cannot be simplified any more than that.

4x2 + x2 = 8 + x2

-3

y=4x2+3x+8

4x2+20x+25 (2x+5)^2

4x2 + 12x + 5 = (2x + 1)(2x + 5).

x3 + 4x2 + 6x + 24 = (x2 + 6)(x + 4)

x3 + 4x2 + x + 4 = (x + 4)(x2 + 1)

12

12

8x3 + 4x2 + 6x + 3 = 4x2(2x + 1) + 3(2x + 1) = (2x + 1)(4x2 + 3)

(x + 3)(7x^2 + 1)

4x2-x+2x2 is 6x2-x when simplified

The quadratic 4x2+24x+11 = (2x+1)(2x+11)

4x2+49x+90 = (4x+9)(x+10) when factored

7x3 equals 21.

4x2+3x+6+5x+3x+6 = 4x2+11x+12 when simplified

8 (eight)

11

4x2-4x+1 = (2x-1)(2x-1)

(4x2)+ (28xy) + (49y2) = (2x + 7y)(2x + 7y) = (2x + 7y)2

I assume you mean factors for 4x2+10x+6.(2x+3)(2x+2).